Heavy Metal Concentration in Airborne Particles at Nursery Schools in Hanoi and Health Risk Assessment - Trinh, Tran Dinh; Men, Nguyen Thi Thuy (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 1, 2019)
Indoor air quality is increasingly important as people spend more and more time on indoor activities.  A sampling campaign was conducted to sample airborne particles at nursery schools in Hanoi in May and June, 2018. The sampling strategy was performed both in the presence and in the absence of children in classrooms. Heavy metals and trace elements (Cu, Pb, Cd, Zn, Ni, As, Mn, Cr, Hg, Fe…) were quantified using ICP-MS method. Emission sources of heavy metals were estimated using statistical analyses such as factor analysis while cancer risk assessment was conducted using chronic daily intake (CDI) and slop factor (SF). In the presence of children, indoor concentrations of heavy metals and trace elements ranged from 1.7-3.2 ng/m 3 (Cd) to 1,588-3,238 ng/m 3 (Zn), while the corresponding values obtained when the rooms were empty, ranged from 0.6-0.9 to 746.2-2,011 ng/m 3 . Indoor/outdoor ratios of the studied elements varied from school to school and ranged from 0.25 to 2.88, implying the presence of indoor emission sources. The calculated cancer risks ranged from 4.8x10 -6 to 5.0x10 -4 , higher than the limit values set by USEPA, implying a significant health risk to young children. Keywords Indoor air quality, heavy metals, ICP-MS, health risk, young children, Hanoi References [1] M.T. Latif, S.M. Yong, A. Saad, N. Mohamad, N.H. Baharudin, M.B. Mokhtar, N.M. Tahir, Composition of heavy metals in indoor dust and their possible exposure: a case study of preschool children in Malaysia, Air Quality, Atmosphere and Health. 7 (2014) 181-193. [2] B.K.K. Perihan, Determination of heavy metals in indoor dust from Istanbul, Turkey: Estimation of the health risk, Environment International. 50 (2012) 47–55. [3] A. Kamkar, B. Noudoost, G. Bidhendi et al., Monitoring of heavy metals in raw milk of vet husbandries in industrial regions of Isfahan Province of Iran, Asian J Chem. 22 (2010) 7927-7931. [4] F.M. Darus, R.A. Nasir, S.M. Sumari et al., Heavy metals composition of indoor dust in nursery schools building, Procedia Soc Behav Sci. 38 (2012) 169-175. [5] W.W. Nazaroff, Indoor particle dynamics, Indoor Air. 14 (2004) 175–183. [6] G.J. Keeler, J.T. Dvonch, F.Y. Yip et al., Assessment of personal and community-level exposures to particulate matter among children with asthma in Detroit, Michigan, as part of Community Action Against Asthma (CAAA), Environ. Health Perspect. 110 (2002) 173–181. [7] T. Li, S. Cao, D. Fan et al., Household concentrations and personal exposure of PM2.5 among urban residents using different cooking fuels, Science of the Total Environment. 548–549 (2016) 6–12. [8] J.L. Adgate, G. Ramachandran, G.C. Pratt et al., Longitudinal variability in outdoor, indoor, and personal PM2.5 exposure in healthy non–smoking adults, Atmospheric Environment. 37 (2003) 993- 1002. [9] J.J. Cao, S.C. Lee, J.C. Chow et al., Indoor/ outdoor relationships for PM2.5 and associated carbonaceous pollutants at residential homes in Hong Kong, Indoor Air. 15 (2005) 197–204. [10] H. Fromme, D. Twardella, S. Dietrich et al., Particulate matter in the indoor air of classrooms-exploratory results from Munich and surrounding area, Atmos. Environ. 41 (2007) 854–866. [11] K.C. Coombs, G.L. Chew, C. Schaffer et al., Indoor air quality in green-renovated vs. non-green low-income homes of children living in a temperate region of US (Ohio), Total Environ. 554–555(2016), 178–185. [12] P.T.B.S. Branco, M.C.M. Alvim-Ferraz, F.G. Martins, S.I.V. Sousa, Indoor air quality in urban nurseries at Porto city: particulate matter assessment, Atmos. Environ. 84 (2014), 133–143. [13] W.H. Yang, J. Sohn, J.W. Kim, B. Son, and J. Park, Indoor air quality investigation according to age of the school buildings in Korea, J. Environ. Manage. 90 (2009) 348–354. [14] R. Goyal, M Khare, Indoor-outdoor concentrations of RSPM in classroom of a naturally ventilated school building near an urban traffic roadway, Atmos. Environ. 43 (2009) 5989–6120. [15] M. Branis, J. Safranek, A Hytychova, Exposure of children to airborne particulate matter of different size fractions during indoor physical education at school, Build. Environ. 44 (2009) 1246–1252. [16] D.T. Tran, L.Y. Alleman, P. Coddeville, J.C. Galloo, Elemental characterization and source identification of size resolved atmospheric particles in French classrooms, Atmospheric Environment. 54 (2012) 250–259. [17] T.Y. Susanna, U. Tong, C.L. Kin, Are nursery schools and kindergartens safe for our kids? The Hong Kong study, The Science of the Total Environment. 216 (1998) 217–225. [18] L. Xinwei, Z. Xiaolan, Y. L. Loretta, C. Hao, Assessment of metals pollution and health risk in dust from nursery schools in Xi’an, China, Environmental Research. 128 (2014) 27–34. [19] H. Zhangxiong, W. Dejun, Y. Jinsong, L. Xingqi, Heavy Metal Pollution in Settled Dust Associated with Different Urban Functional Areas in a Heavily Air-Polluted City in North China, Environmental Research and Public health. 13 (2016) 50–63. [20] D.T. Tran, L.Y. Alleman, P. Coddeville, J.C. Galloo, Indoor-outdoor behavior and sources of size-resolved airborne particles in French classrooms, Building and Environment. 81 (2014) 183–191. [21] U.S. EPA, Exposure Factors Handbook 2011 Edition (Final Report), U.S. Environmental Protection Agency, Washington, DC, EPA/600/R-09/052F, 2011. [22] S.I.V. Sousa, C. Ferraz, M.C.M. Alvim-Ferraz, L.G. Vaz, A.J. Marques and F.G. Martins, Indoor air pollution on nurseries and primary schools: impact on childhood asthma – study protocol, BMC Public Health. 12 (2012) 435.